2000
DOI: 10.1021/es000013c
|View full text |Cite
|
Sign up to set email alerts
|

Heavy Metal Adsorption by Functionalized Clays

Abstract: Organic ligands containing the thiol (-SH) metal-chelating functionality were either grafted to the external surface silanol groups of sepiolite or introduced in the interlayers of montmorillonite, and the resulting functionalized clays were characterized and assayed as adsorbents for Hg(II), Pb(II), and Zn(II) ions from solution. Sepiolite was functionalized by covalently grafting 3-mercaptopro-pyltrimethoxysilane (MPS) to the surface tSi-OH groups of the clay, whereas montmorillonite was functionalized by re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
186
0
2

Year Published

2008
2008
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 361 publications
(195 citation statements)
references
References 23 publications
(59 reference statements)
7
186
0
2
Order By: Relevance
“…Among all the approaches proposed, adsorption is one of the most popular methods and is currently considered as an effective, efficient, and economic method for water purification. The adsorbents used include activated carbon (Nouri et al, 2002;Pereira et al, 2003), clay minerals (Celis et al, 2000;Abollino et al, 2003), zeolites (Oliveira et al, 2004), metal oxides (Wu et al, , 2005Zhang et al, 2007a), agricultural wastes (Robinson et al, 2002), biomass (Loukidou et al, 2003) and polymeric materials (Atia et al,2003).…”
Section: Introductionmentioning
confidence: 99%
“…Among all the approaches proposed, adsorption is one of the most popular methods and is currently considered as an effective, efficient, and economic method for water purification. The adsorbents used include activated carbon (Nouri et al, 2002;Pereira et al, 2003), clay minerals (Celis et al, 2000;Abollino et al, 2003), zeolites (Oliveira et al, 2004), metal oxides (Wu et al, , 2005Zhang et al, 2007a), agricultural wastes (Robinson et al, 2002), biomass (Loukidou et al, 2003) and polymeric materials (Atia et al,2003).…”
Section: Introductionmentioning
confidence: 99%
“…Conversely, Celis et al . [8] did not find a significant difference between adsorption of mercury in the presence of up to 0.1 M NaNO 3 (8.5 g L − 1 ) and the adsorption measured in the absence of the electrolyte. On the other hand, Echeverría et al .…”
Section: Effect Of Salinity On Hg(ii) Adsorptionmentioning
confidence: 65%
“…Because of the physical and chemical characteristics of clay minerals, such as large surface area, moderate to high cation exchange capacity and high negative surface charge, these materials can act as concentrators of trace elements in aquatic ecosystems [6], and can play an important role in controlling the background levels of such trace elements in sediments [7]. In addition, other features of these materials include their common occurrence in soils and sediments from most ecosystems and low cost [8]. Hirst [7] suggested that clay minerals concentrate trace elements in the sequence: montmorillonite > vermiculite > illite = chlorite > kaolinite.…”
Section: Introductionmentioning
confidence: 99%
“…bentonite, kaolinite, montmorillonite, wollastonite) (CELIS et al, 2000;PRADAS et al, 1994), human hair and teeth (HELAL et al, 2002;TAN et al, 1985), leaf mould (SHARMA and FORSTNER, 1994), sand (AWAN et al, 2003), metal oxides (Al, Fe, Mn -oxides) (BAILEY et al, 1992;TRIVEDI andAXE, 2001), vermicompost (PEREIRA andARRUDA, 2003), xanthate (FLYNN et al, 1980;JAWED and TARE, 1991), and zeolites (e.g., clinoptilolite and chabazite) (GENÇ-FUHRMAN, 2007;LEPPERT, 1990;KALLO, 2001;OLIVEIRA et al, 2004).…”
Section: Miscellaneous Sorbentsmentioning
confidence: 99%